2022
DOI: 10.3389/fnagi.2022.924984
|View full text |Cite
|
Sign up to set email alerts
|

Non-linear association between serum spermidine and mild cognitive impairment: Results from a cross-sectional and longitudinal study

Abstract: BackgroundAlthough animal studies show that spermidine (SPD) affects cognitive function, the relevant evidence among humans is limited. We aim to examine the association between serum SPD levels and cognitive performance.Materials and MethodsWe conducted a cross-sectional and longitudinal study including a baseline and one follow-up survey. The baseline survey was conducted from June 2019 to August 2019, while the follow-up survey was conducted from June 2021 to August 2021. We analyzed 3,774 adult participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…This fact was questioned in a letter to the editor due to too low R 2 levels in the correlation analysis carried out [ 4 ]. A recently published study with a sample size of 3774 also described a correlation between serum spermidine levels and cognitive impairments [ 5 ]. In addition, the authors concluded that monitoring the spermidine levels may be helpful for reducing the incidence of cognitive impairments.…”
Section: Discussionmentioning
confidence: 99%
“…This fact was questioned in a letter to the editor due to too low R 2 levels in the correlation analysis carried out [ 4 ]. A recently published study with a sample size of 3774 also described a correlation between serum spermidine levels and cognitive impairments [ 5 ]. In addition, the authors concluded that monitoring the spermidine levels may be helpful for reducing the incidence of cognitive impairments.…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, one research group demonstrated that in 43 samples from American individuals over 65 years old at the Oregon Alzheimer's Disease Center, an increase in serum levels of spermidine corresponded to the progression from MCI to AD (Figure 2 and Table 1), suggesting the viability of measuring serum spermidine as a key molecule in AD pathology and as a potential biomarker for AD progression [36]. On the other hand, a study with a rural Chinese population of approximately 3,700 individuals over 35 years old with no history of dementia revealed a non-linear relationship between spermidine and MCI, implying that high levels of spermidine may decrease the burden of MCI (Table 1) [69]. These contradictory reports raise the possibility that factors such as race, diet, and geographic location could change the general perspective on the role of spermidine in AD or MCI.…”
Section: The Role Of Pas In Alzheimer's Diseasementioning
confidence: 99%
“…years. There was an albeit non-linear, positive correlation between spermidine levels and the risk of mild cognitive impairment [20]. Higher dietary intake of spermidine was associated with greater hippocampal volume, greater mean cortical thickness, and greater cortical thickness in parietal and temporal lobes, which are common ADaffected regions, independently of cognitive performance [21].…”
Section: Introductionmentioning
confidence: 98%